2022
DOI: 10.17648/acta.scientiae.6745
|View full text |Cite
|
Sign up to set email alerts
|

Math Anxiety in Primary Education during Covid-19 Confinement: Influence on Age and Gender

Abstract: Background:The closure of schools in Spain due to the Covid-19 pandemic confronted teachers, students, and families with a new reality. Previous studies have shown that anxiety levels increase during pandemic times. Therefore, it highlights the interest of the affective domain in primary education. Objectives: To analyse some general aspects of math anxiety, such as primary school students' fear, nervousness, and blockage before mathematics both at the educational centre and at home during the Covid-19 confine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“… Mamolo (2022) found that the students’ math motivation and self-efficacy decreased during the pandemic. Similarly, Mendoza et al (2021) and Arnal-Palacián et al (2022) provided evidence about higher levels of math anxiety experienced by university and primary school students, respectively, during Covid-19.…”
Section: Methodsmentioning
confidence: 89%
“… Mamolo (2022) found that the students’ math motivation and self-efficacy decreased during the pandemic. Similarly, Mendoza et al (2021) and Arnal-Palacián et al (2022) provided evidence about higher levels of math anxiety experienced by university and primary school students, respectively, during Covid-19.…”
Section: Methodsmentioning
confidence: 89%